A review of internet of medical things (IoMT) - based remote health monitoring through wearable sensors: a case study for diabetic patients - Omar AlShorman; Buthaynah AlShorman; Mahmood Al-khassaweneh; Fahad Alkahtani (Institute of Advanced Engineering and Science, 2020)
The latest advances and trends in information technology and communication have a vital role in healthcare industries. Theses advancements led to the internet of medical things (IoMT) which provides a continuous, remote and real-time monitoring of patients. The IoMT architectures still face many challenges related to the bandwidth, communication protocols, big data and data volume, flexibility, reliability, data management, data acquisition, data processing and analytics availability, cost effectiveness, data security and privacy, and energy efficiency. The goal of this paper is to find feasible solutions to enhance the healthcare living facilities using remote health monitoring (RHM) and IoMT. In addition, the enhancement of the prevention, prognosis, diagnosis and treatment abilities using IoMT and RHM is also discussed. A case study of monitoring the vital signs of diabetic patients using real-time data processing and IoMT is also presented.